Syncope and undifferentiated shock. Issue 2 (10th March 2021) - Trotzky, Daniel; Amer, Ali; Fraij, Salha; Fordham, Daniel E.; Granovsky, Gregory; Aizik, Uri; Carady, Natali; Cohen, Aya; Fuchs, Shmuel; Mengesha, Bethlehem; Burgsdorf, Oleg; Yofik, Inna; et al.
Abstract: Ventricular free wall rupture is a rare post myocardial complication with a high associated mortality. In this article we discuss the case of an elderly patient who presented to our emergency department in shock after an episode of syncope. Using Point Of Care Ultrasound (POCUS), identification of cardiac tamponade and pericardial thrombus was possible, signs indicating a diagnosis of free wall rupture. Early initiation of transfer proceedings to a tertiary cardio‐thoracic unit was therefore possible, resulting in a positive patient outcome.